2009
DOI: 10.1111/j.1600-0625.2009.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Depth profiling of Stratum corneum hydration in vivo: a comparison between conductance and confocal Raman spectroscopic measurements

Abstract: The high-frequency electrical conductance of tapestripped human skin in vivo can be used to evaluate the hydration profile of Stratum corneum (SC). Tape-stripping provides access to the underlying SC layers, and the conductance of these layers (as measured by the Skicon instrument) correlates well with their water content, as demonstrated by independent confocal Raman spectroscopic measurements. The correlation shows high interindividual variance and is not linear over the full measurement range of the instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 40 publications
(55 reference statements)
1
45
0
Order By: Relevance
“…6A; F likely to acclimatize to changes in temperature and humidity and thus maintain heat and water balance even in cold, dry conditions. In both winter-and summer-acclimatized house sparrows, the amount of water increased linearly with SC depth, a pattern that is consistent with studies done on humans (Warner et al, 1988;Boncheva et al, 2009). This increase in water content was positively correlated with the number of gauche defects present in the associated lipid lamellae.…”
Section: Lipidssupporting
confidence: 75%
See 1 more Smart Citation
“…6A; F likely to acclimatize to changes in temperature and humidity and thus maintain heat and water balance even in cold, dry conditions. In both winter-and summer-acclimatized house sparrows, the amount of water increased linearly with SC depth, a pattern that is consistent with studies done on humans (Warner et al, 1988;Boncheva et al, 2009). This increase in water content was positively correlated with the number of gauche defects present in the associated lipid lamellae.…”
Section: Lipidssupporting
confidence: 75%
“…Although most studies correlating barrier properties of the SC with lipid composition have assumed uniform water flux and lipid composition throughout the thickness of the SC, several studies on human SC have shown that water content increases in deeper layers of the SC (Warner et al, 1988;Bommannan et al, 1990;Boncheva et al, 2009). Furthermore, tape-stripping experiments on human SC show that overall lipid content decreases with depth in the uppermost 2 µm of the SC as corneocyte volume increases, and remains constant thereafter (Bommannan et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…9,15,[26][27][28][29][30] Given that skin is able to take up water, it is reasonable to assume that water should also change its morphology and surface properties. In order to analyze these changes over time, we have employed 3D laser scanning microscopy, which allowed us to observe the surface of a skin replica under high magnification and provided 3D information.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al showed good validation of water content measurement between CRS and Karl Fischer method [21]. Boncheva et al also showed correlation between CRS and skin conductance related to water content measurement [22]. As optical coherence tomography (OCT) has been widely used for measurement of epidermal thickness [23][24][25][26][27], Crowthers et al published a validation study for SC thickness measurement between CRS and OCT [19].…”
Section: Introductionmentioning
confidence: 99%